Norepinephrine Enhances Radiosensitivity in Rat Ileal Epithelial Cells - MATSUU-MATSUYAMA, Mutsumi; OKAICHI, Kumio; SHICHIJO, Kazuko; NAKAYAMA, Toshiyuki; NAKASHIMA, Masahiro; SEKINE, Ichiro (JOURNAL OF RADIATION RESEARCH, 2011)
We previously reported that the apoptosis index in jejunal crypt cells after X irradiation was greater in spontaneously hypertensive rats than in Wistar-Kyoto rats. Moreover, these same cells showed a suppression of apoptosis when reserpine was administered to induce sympathetic dysfunction in spontaneously hypertensive rats or Wistar-Kyoto rats1). Whether the hyperfunction of the sympathetic nervous system is involved in the high susceptibility of the jejunal crypt cells to radiation-induced apoptosis was the subject of this study. The effect of norepinephrine (NE) on cell survival was examined using the colony formation assay after X-ray irradiation of rat ileal epithelial cells (IEC-18). The addition of 1μM NE decreased the surviving fraction of cells irradiated with 6Gy from 37% to 8%. The radiosensitivity of IEC-18 cells was enhanced by the addition of 1μM of NE. The irradiation and treatment with NE also resulted in an increased cellular apoptotic rate. These results showing enhanced radiosensitivity of rat ileal epithelial cells by NE suggest that NE may be one of the factors which aggravate acute radiation injury in the intestine. [INTRODUCTION] Spontaneously hypertensive rats, originally derived from Wistar Kyoto rats, are a well-known model for studying essential hypertension in humans.